Association Between Traditional Herbal Diet and Nasopharyngeal Carcinoma Risk: A Prospective Cohort Study in Southern China - Lyu, Yun-Hong; Lin, Chu-Yang; Xie, Shang-Hang; Li, Tong; Liu, Qing; Ling, Wei; Lu, Yu-Qiang; Cao, Su-Mei; Lin, Ai-Hua (Frontiers in Oncology, 2021)
Introduction: Prospective evidence for herbal diet and nasopharyngeal carcinoma (NPC) development is absent. We therefore evaluated the associations of herbal soup and herbal tea with NPC in a prospective cohort study in southern China. Methods: Based on an NPC screening cohort established in 2008-2015, information on herbal diet consumption, potential confounding factors and Epstein-Barr virus (EBV) antibody levels were collected from 10,179 individuals aged 30-69 years in Sihui city, southern China. Cox regression models were performed to examine herbal diet with NPC risk, and logistic regression models were used to examine herbal diet with EBV reactivation. Results: During a median of 7.54 years of follow-up, 69 participants developed NPC. Herbal soup consumption was associated with decreased NPC risk, with HRs of 0.31 (95%CI: 0.15-0.62) for the highest intake frequency and 0.29 (95%CI: 0.16-0.51) for a longer duration. But herbal tea was not significantly associated. Moreover, we identified herbal soup was inversely associated with EBV seropositivity among all the participants at baseline, with the adjusted ORs were 0.78 (95%CI: 0.65-0.93) for VCA-IgA and 0.76 (95%CI: 0.64-0.91) for EBNA1-IgA in those with the highest frequency; 0.70 (95%CI: 0.59-0.84) for VCA-IgA and 0.64 (95%CI: 0.54-0.77) for EBNA1-IgA in those with the longer duration. Inverse associations were also observed in non-NPC individuals. Conclusions: With inhibition of EBV reactivation by plants, herbal soup could significantly decrease the risk of NPC in endemic areas.